Implementasi Projek Penguatan Profil Pelajar Pancasila Sebagai Penguatan Pendidikan Karakter - Saifullah, Ahmad; Djatmika, Eri Tri; Pristiani, Riska (Jayapangus Press, 2024)
The initiative aims to analyze the implementation of the Pancasila Student Profile Enhancement Project (P5) in student character formation. The qualitative approach is used in the initiation of the SDN of the First Grade I, using observations, interviews, and documentation as data collection techniques. Successfully collected data is analyzed through a series of stages, including data reduction, data presentation, and verification, with the aim of generating conclusions based on findings during the study. Research results show that implementation of P5 involves measures such as design, management, assessment, evaluation, and follow-up. The P5 theme focuses on sustainable lifestyles and local wisdom, with specialized modules covering data literacy, digital literature, and humanism literacy. P5 management in High School I includes team formation, identification of school readiness, character dimension selection, theme determination, and implementation time allocation. Formative and sumative assessments are used to evaluate student character development, while evaluation involves identifying weaknesses and monitoring student skills. The final evaluation and follow-up involves character strengthening and the continuation of positive practices through the Mari Actions program. The further action of Mari Acts is expected to be a means and a positive habit in strengthening the character of the pupils, in line with the character profile of Pancasila students. This research provides an in-depth overview of the implementation of P5 as a character education strategy in SDN Tunggulwulung I, providing inspiration and reference for other schools that want to adopt P5 to strengthen student character education.